2017
DOI: 10.5812/asjsm.42091
|View full text |Cite
|
Sign up to set email alerts
|

The Calculation of the Uphill Energy Cost of Running from the Level Energy Cost of Running in a Heterogeneous Group of Mountain Ultra Endurance Runners

Abstract: Ultra-endurance mountain running has become extremely popular in recent years, and the energy cost is one of the factors that influence the final performance. The aim of this study was to determine if the energy cost of uphill running (uphill Cr) can be calculated from level Cr (Energy cost of running in mLO2.kg -1 .mn -1 ) in a heterogeneous group of mountain ultra-endurance runners using the di Prampero equation, and if fatigue could change this relationship. Twenty-four male ultra-trail runners ran on a lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 7 publications
2
13
1
Order By: Relevance
“…These results are interesting for training purposes while considering AS as an intensity index during training sessions. In line, previous studies reported a linear increase in energy cost with each increment (4,20,25). The greater energy cost at a same absolute AS may result from the higher muscular mass involved while increasing the sloped gradient (22, 50, 52).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are interesting for training purposes while considering AS as an intensity index during training sessions. In line, previous studies reported a linear increase in energy cost with each increment (4,20,25). The greater energy cost at a same absolute AS may result from the higher muscular mass involved while increasing the sloped gradient (22, 50, 52).…”
Section: Discussionsupporting
confidence: 91%
“…A standardized warm-up program of 15 minutes preceded each test. The 3 tests were performed on a motorized treadmill (Intelligent Suspension 3, Cybex International Inc., MA) as follows (2): incremental test (IT01) starting at 8 km·h −1 with a progressive increase of 1 km·h −1 every minute and an inclination of 1% (3); incremental test (IT10) starting at an AS of 500 m·h −1 with a progressive increase of 100 m·h −1 every minute with an inclination of 10%; and (4) incremental test (IT25) starting at an AS of 500 m·h −1 with a progressive increase of 100 m·h −1 every minute with an inclination of 25%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review on physiological determinant of TR performance suggested to include more specific TR tests, such as incline Cr, in future research focusing on TR performance (11). Interestingly, since level and uphill Cr have been shown to be correlated in experienced (40) and in elite (44) but not in high-level (1) trail runners, it is worth investigating Cr in both level and graded running conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ski mountaineering (Ski-Mo), Nordic-Cross Country (NCC), and Biathlon (Bia) are known to be the most challenging winter sports because they involve whole-body movements, uphill locomotion, and altitude environments [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%